2013
DOI: 10.1007/s11079-013-9285-5
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated vs. Anticipated Tax Reforms in a Two-Sector Open Economy

Abstract: We use a two-sector neoclassical open economy model with traded and non-traded goods to investigate the effects of unanticipated and anticipated tax reforms. First, an unanticipated tax reform produces an expansion of GDP, labor, and investment, while an anticipated tax reform has opposite effects before the implementation of the labor tax cut. Quantitatively, if the traded sector is more capital intensive, GDP increases by 1.6 percentage points or declines by 2.7 percentage points after three years, depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Since the household's maximization problem is identical to that described in section 2, we restrict our attention to the firms' maximization problem. More technical details can be found in the working paper version of the paper by Cardi and Restout [2014], [2015].…”
Section: N Solving the Model With Endogenous Markupsmentioning
confidence: 99%
“…Since the household's maximization problem is identical to that described in section 2, we restrict our attention to the firms' maximization problem. More technical details can be found in the working paper version of the paper by Cardi and Restout [2014], [2015].…”
Section: N Solving the Model With Endogenous Markupsmentioning
confidence: 99%
“…Later, the reform stimulates the economy. Based on this finding, Cardi and Restout (2014) showed that, in an open economy, a switch from labour taxes to consumption taxes leads to a greater rise in GDP if the reform is unannounced. Our result is in line with these findings; however, in contrast, our results are determined by increased personal savings, which function as an externality since they reduce interest rates.…”
Section: Introductionmentioning
confidence: 99%